2016
DOI: 10.18632/oncotarget.12925
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress-induced neuronal inflammatory response and apoptosis likely plays a key role in the development of diabetic encephalopathy

Abstract: We assumed that diabetic encephalopathy (DEP) may be induced by endoplasmic reticulum (ER)-mediated inflammation and apoptosis in central nervous system. To test this notion, here we investigated the neuronal ER stress and associated inflammation and apoptosis in a type 2 diabetes model induced with high-fat diet/streptozotocin in Sprague-Dawley rats. Elevated expressions of ER stress markers, including glucose-regulated protein 78 (GRP78), activating transcription factor-6 (ATF-6), X-box binding protein-1 (XB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…The purpose of using 4-PBA in the present study was solely to reduce ER stress, as in previous studies [ 45 , 46 ]. Indeed, Bohnert et al [ 47 ] showed that 4-PBA decreased muscle mass in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of using 4-PBA in the present study was solely to reduce ER stress, as in previous studies [ 45 , 46 ]. Indeed, Bohnert et al [ 47 ] showed that 4-PBA decreased muscle mass in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular chaperones participate in the folding process of protein through recognizing, retaining and targeting mis-folded proteins for their eventual degradative pathway (Welch and Brown, 1996). Chemical chaperone 4-PBA prevents the aggregation of mis-folded proteins and corrects folding of proteins to get their right conformation, which is commonly used to alleviate ER stress (Wang et al, 2016). 4-PBA is also a histone deacetylase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…NFB induction by SR/ER stress is prevented by pre-incubation of cells with intracellular Ca 2+ chelators, suggesting that Ca 2+ release precedes ROS formation in the NFB-mediated SR/ER-nuclear signal transduction pathway [112]. Several studies have demonstrated that hypoxia/reoxygenation is sufficient to induce SR/ER stress [113] [114]. NFB acts as a link between SR/ER stress and inflammation after hypoxia/reoxygenation.…”
Section: F Upr-regulated Oxidative Protein Folding Machinery In the mentioning
confidence: 99%